Playful methods : engaging the unexpected in literacy research - Medina, Carmen Liliana; Perry, Mia.; Wohlwend, Karen E. (New York : Routledge, 2022)
This book introduces three new subjects to the context of literacy research--play, the imaginary, and improvisation--and proposes how to incorporate these important concepts into the field as research methods in order to engage people, materials, spaces, and imaginaries that are inherent in every research encounter. Grounded in cutting-edge theory, chapters are structured around lived narratives of research experiences, demonstrating key practices for unsettling and expanding the ways people interact, behave, and construct knowledge. Through an exploration of difference, play, and the imaginary, authors Medina, Perry, and Wohlwend present an active set of practices that acknowledges and attends to the global, fragmented, politicized contexts in literacy research. This book provides researchers and literacy education scholars with rich and clear theoretical foundations and practical tools to engage in literacy research in ethical, creative, and responsive ways. The authors invite readers to play by exploring the ways in which pedagogical, research, artistic, and other creative contexts can be sites to examine identity, plurality, and difference. Chapters feature innovative elements such as author dialogues that make visible how the authors engage with the ideas they present; guiding questions to prompt reflection and conversation; playful invitations to share possibilities of play in real-world contexts; and stories and practices to ground the conceptual and playful inquiry.
Part I. The (play)ground. Invitations to play and reimagine inquiry for lived literacies -- The research encounter : difference and relation -- Imaginaries and the imagination in literacy research encounters -- Methods for designing the research (play)ground -- Part II. PLayful methods across contexts. Improvisation as inquiry spaces for (un)doing literacy and doing humanizing work -- Play, ruptures, and becomings -- Taking playful methods into the wild -- Uncertain futures and unsatisfying conclusions.
Keywords: Literacy -- Research; EDUCATION / General; EDUCATION / Research; EDUCATION / Philosophy & Social Aspects